Study on a Simultaneously Solving Model for Stratified Air Conditioning under Low Sidewall Air Supply System in a Large Space Building (Zhileng xuebao)
A simultaneously solving model is presented under the low sidewall air supply system of thermal stratification environment in large space building.The model is used to predict indoor vertical air temperature and inner surface temperature,as well as the cooling load.Through the summer experiment in a large space building,the indoor air vertical temperature,inner surface temperature and cooling load are tested,the calculated results of simultaneously solving model are compared with the test data,and the resul...